2017
DOI: 10.1097/md.0000000000008758
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of iontophoretic corneal collagen crosslinking in keratoconic eyes with very thin corneas

Abstract: The purpose of this retrospective study was to report the results of iontophoretic corneal collagen crosslinking (I-CXL) with riboflavin and ultraviolet A irradiation in patients affected by keratoconus, each with thinnest pachymetry values of <400 μ (with epithelium) and not treatable using standard epithelium-off technique.Fifteen eyes of 15 patients affected by progressive keratoconus and with thinnest pachymetry values <400 μ underwent I-CXL. The uncorrected (UDVA) and corrected (CDVA) distance visual acui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The assessment of endothelial cell density (ECD) loss in standard and accelerated and transepithelial CXL protocols in the pediatric group has not produced a statistically significant decrease in ECD after the procedure [ 21 , 23 , 56 , 58 , 61 , 69 , 70 , 76 , 80 , 82 , 96 , 97 ]; however, other studies reported that, depending on the protocol and carrier used, there is damage to endothelial cell density [ 68 , 98 100 ]. In a retrospective SCXL study developed by Barbisan et al in 2020, involving 105 eyes, a statistically significant reduction in ECD was observed, as well as corneal thinning after 1 year of follow-up, evidencing the potential impact of CXL on anatomy and corneal physiology [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…The assessment of endothelial cell density (ECD) loss in standard and accelerated and transepithelial CXL protocols in the pediatric group has not produced a statistically significant decrease in ECD after the procedure [ 21 , 23 , 56 , 58 , 61 , 69 , 70 , 76 , 80 , 82 , 96 , 97 ]; however, other studies reported that, depending on the protocol and carrier used, there is damage to endothelial cell density [ 68 , 98 100 ]. In a retrospective SCXL study developed by Barbisan et al in 2020, involving 105 eyes, a statistically significant reduction in ECD was observed, as well as corneal thinning after 1 year of follow-up, evidencing the potential impact of CXL on anatomy and corneal physiology [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…I-CXL represents an attractive solution for patients with thinner corneas. Cantemir et al [51] treated 15 keratoconus patients, each with thinnest pachymetry values of \ 400 lm (with epithelium) and not treatable using S-CXL technique. The mean UDVA and CDVA significantly increased 12 months after I-CXL and K max readings significantly decreased until the last follow-up (12 months).…”
Section: I-cxl On Special Groups Of Patientsmentioning
confidence: 99%
“…4,5 Therefore, several modifications of the standard protocol have been proposed to achieve safe and effective stabilization in progressive keratoconus patients with thin corneas (<400 μm). These modifications include stromal swelling using hypo-osmolar riboflavin, 6 transepithelial and iontophoretic CXL, 7,8 contact lens-assisted CXL, 9 pachymetric-guided epithelial debridement, 10 lenticule-assisted CXL, 11 and the recently introduced individualized CXL (sub400 protocol). 12 Jacob et al 9 introduced a simple technique called contact lens-assisted CXL (CL-CXL), which provides safe and effective CXL in even ultra-thin corneas without the need for stromal swelling.…”
Section: Introductionmentioning
confidence: 99%